Evaluation of a C-reactive protein latex agglutination detection test with sera from patients with sexually transmitted diseases. - Schalla, W O (1984)
A total of 149 sera, including 79 pre- and posttreatment sera from 33 patients with disseminated gonococcal infections, 18 from patients with uncomplicated gonococcal infections, 6 from patients with pelvic inflammatory disease, 4 from patients with genital Chlamydia trachomatis infections, and 42 from normal volunteers, were examined for C-reactive protein with a latex agglutination C-reactive protein detection kit (Difco Laboratories, Detroit, Mich.). Results were quantitated with LC-Partigen C-reactive protein radial immuno-diffusion plates (Calbiochem-Behring, La Jolla, Calif.). Positive latex agglutination results were observed in all of the pretreatment sera and some of the posttreatment sera of patients with disseminated gonococcal infections and in two sera from patients with pelvic inflammatory disease, which corresponded to quantitative C-reactive protein levels in the radial immunodiffusion plates. C-reactive protein levels were not detectable in the serum samples from normal volunteers or patients with uncomplicated gonococcal infections or genital chlamydial infections. Positive latex agglutination occurred as early as 20 s in sera with high C-reactive protein levels, and all positive results were observed within 90 s of the 3-min test limit. Positive latex test results were obtained with C-reactive protein levels as low as 1 mg/dl (10 micrograms/ml).